A Framework for Approaching Mixed Methods Intervention Research to Address the Emotional and Behavioral Health Needs of Children. (May 2023) - Houchins, David E.; Hitchcock, John H.; Conroy, Maureen A.
The use of singular methodologies has dominated emotional and behavioral disorder (EBD) intervention research, and by extension, the field has not deployed mixed-methods research (MMR). The purpose of this article is to provide an overview of MMR and demonstrate its utility for conducting EBD intervention research. The basic tenants and design principles of MMR are discussed. Then, we present an aspirational framework that summarizes 17 areas where MMR can be applied to EBD intervention research using a school psychology study for illustration. The framework includes (a) research question development, (b) intervention development, (c) instrumentation development, (d) selection, (e) sampling, (f) multi-lens causality, (g) social validity, (h) acceptability, (i) stakeholder perspectives, (j) treatment integrity, (k) contamination, (l) carry-over effects, (m) outcome variability, (n) attrition, (o) replication, (p) data analysis and interpretation, and (q) dissemination. By referring to this framework as being aspirational, we mean to convey that very few social science studies or programs of research fully address all its elements; indeed, it may even be considered as a wish list. However, we contend that MMR approaches can help researchers to address the framework more fully within their lines of EBD inquiry.